SOLID-STATE (1H AND 13C) NUCLEAR MAGNETIC RESONANCE SPECTROSCOPY OF INSOLUBLE ORGANIC RESIDUE IN THE MURCHISON METEORITE: A SELF-CONSISTENT QUANTITATIVE ANALYSIS - Cody G.D.; Alexander C.M.O.; Tera F. (My University, 2002)
Complementary, double- and single-resonance solid-state (1H and 13C) nuclear magnetic resonance (NMR) experiments were performed on a solvent extracted and demineralized sample of Murchison meteorite organic macromolecule. These NMR data provide a consistent picture of a complex organic solid composed of a wide range of organic (aromatic and aliphatic) functional groups, including numerous oxygen-containing functional groups. The fraction of aromatic carbon within the Murchison organic residue (constrained by three independent experiments) lies between 0.61 and 0.66. The close similarity in cross-polarized and single-pulse spectra suggests that both methods detect the same distribution of carbon. With the exception of interstellar diamond (readily detected in slow magic angle spinning single-pulse NMR experiments), there is no evidence in the solid-state NMR data for a significant abundance of large laterally condensed aromatic molecules in the Murchison organic insoluble residue. Given the most optimistic estimation, such carbon would not exceed 10% and more likely is a fraction of this maximum estimate. The fraction of aromatic carbon directly bonded to hydrogen is low (~30%), indicating that the aromatic molecules in the Murchison organic residue are highly substituted. The bulk hydrogen content, H/C, derived from NMR data, ranges from a low of 0.53 +/- 0.06 and a high of 0.63 +/- 0.06. The hydrogen content (H/C) determined via elemental analysis is 0.53. The range of oxygen-containing organic functionality in the Murchison is substantial. Depending on whether various oxygen-containing organic functional groups exist as free acids and hydroxyls or are linked as esters and ethers results in a wide range in O/C (0.22 to 0.37). The lowest values are more consistent with elemental analyses, requiring that oxygen-containing functional groups in the Murchison macromolecule are highly linked. The combined 1H and 13C NMR data reveal a high proportion of methine carbon, which requires that carbon chains within the Murchison organic macromolecule are highly branched.